The Environmental Protection Agency's Endangered Species Act Affecting Pesticides Specifically for Florida - Frederick M. Fishel (EDIS)
PI-125, a 3-page fact sheet by Frederick M. Fishel, addresses the Environmental Protection Agency's (EPA) voluntary program affecting pesticide use for protecting endangered species in Florida. Currently, there is only one species that is considered for Florida, the Florida torreya, and only Gadsden, Jackson, and Liberty counties are affected. Includes a table of pesticides considered by the EPA to threaten the torreya. Published by the UF Pesticide Information Office, July 2006.